Addressing Algorithmic Bias in Statistical Models: Integrating Technical Solutions with Ethical Governance for Fair AI Systems - Ranjeet Sharma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Recent advancements in machine learning and artificial intelligence have led to the widespread deployment of statistical models across critical decision-making domains, raising significant concerns about algorithmic bias and its societal implications. This comprehensive article examines the multifaceted nature of bias in statistical models, from its origins in data collection and model architecture to its manifestation in real-world applications such as hiring, lending, and criminal justice systems. Through analysis of contemporary case studies and emerging research, it presents a systematic framework for detecting and measuring algorithmic bias, alongside practical strategies for its mitigation. The article introduces novel approaches to fairness-aware machine learning, emphasizing the importance of representative data collection and regular model auditing across demographic groups. This article demonstrates that effective bias mitigation requires a holistic approach combining technical solutions with robust ethical guidelines and regulatory compliance. Furthermore, it explores the legal and organizational responsibilities of developing and deploying fair statistical models, providing actionable insights for practitioners and policymakers. This article contributes to the growing body of literature on algorithmic fairness while offering practical solutions for organizations striving to build more equitable AI systems.